Diseño, desarrollo y construcción de un invernadero hidropónico automatizado para el cultivo de hortalizas en la parroquia Vilcabamba - Ojeda Ordoñez, Sofía Elizabeth (2022)
In the present thesis work, an automated hydroponic greenhouse was developed, perfected and built for the cultivation of vegetables in the Vilcabamba parish, in order to innovate the community with new techniques or cultivation processes. An alternative with great advantages such as: maximum crop yield, higher production, reduction of threats, diseases and human intervention by opting for your own garden in less space. Through the technology used, Internet information was compiled, such as: Institutional bibliographic repository of the UNL, thesis articles, books, reports and videos, additionally consultations with teachers of the Electromechanical Engineering career, about the types of greenhouses, hydroponic techniques and the variables to control. Once the corresponding information had been systematized and considering the proposed data required by the hydroponic greenhouse, the design, selection and construction of hydraulic, electromechanical, electrical and electronic components were carried out. The greenhouse is controlled by three systems: air conditioning, irrigation and ph system, according to the defined variables [humidity, temperature, irrigation (time) and ph], through temperature, humidity, ph and distance sensors they send the signals of control to the Arduino Mega 2560 development board where they are processed with the optimal values established so that if there are variations, they emit control signals to the different activation circuits or actuators present in the greenhouse (mechanical ventilation, electropump, misting, electrovalves for control of ph, curtains and heating) where the results are displayed on the LCD screen. These technological advances that were raised have shown a controlled cultivation, as well as the most effective method to guarantee its quality and production. The greenhouse was designed for a production of 308 lettuces in 18m2. It has a standard modular structure of 6m long, 3m wide and 3.5m high, totally metallic and removable and with the NFT hydroponic technique (nutrient film technique)., considering the proposed data of the system (flow rate for each culture channel 2 L/min). Tables, graphs, screenshots, plans and the programming of the Arduino development board are presented in annexes. Finally, in the experimental phase, the operation of the automated hydroponic greenhouse was validated, achieving expected results. Where a high quality product was obtained and with a harvest production of approximately 96%. Keywords: Automation, NFT hydroponics, automated greenhouses.